Porous NaTi2(PO4)3 Nanocubes Anchored on Porous Carbon Nanosheets for High Performance Sodium-Ion Batteries - Ziqi Wang (Frontiers in Chemistry, 2018)
NaTi2(PO4)3 has attracted great interest as anode material for sodium ion batteries owing to its open three-dimensional framework structure and limited volume changes during the charge and discharge process. However, the poor intrinsic electronic conductivity of NaTi2(PO4)3 needs to be improved for high rate capability. In this work, porous NaTi2(PO4)3 nanocubes anchored on porous carbon nanosheets (NaTi2(PO4)3/C) are designed and developed. This material exhibits a large discharge capacity and good rate capacity including a first discharge capacity of 485 mAh g−1 at a current density of 0.1 A g−1, and 98 mAh g−1 retained at a high rate of 4 A g−1 even after 2,000 cycles. These results suggest that NaTi2(PO4)3/C is a promising anode material for sodium-ion batteries.